Possibility to use solar induced ventilation strategies in tropical conditions by computational fluid dynamic simulation - 310365 Agung Murti Nugroho; Mohd. Hamdan Ahmad, Prof., 1964-; International Conference on Sustainable Environment and Architecture (6th : 2005 : Indonesia) (Skudai : Universiti Teknologi Malaysia, 2005)
03